Antibiotic review kit for hospitals (ARK-Hospital): a stepped wedge cluster randomised controlled trial - Martin, L; Budgell, E; Peto, T; Walker, AS (Elsevier, 2022)
Background: Strategies to reduce antibiotic overuse in hospitals depend on prescribers taking decisions to stop unnecessary antibiotics. There is limited evidence on how to support this. We evaluated a multifaceted behaviour change intervention (ARK) designed to reduce antibiotic use among adult acute/medical inpatients by increasing appropriate decisions to stop antibiotics at clinical review.